Butyric acid production from softwood hydrolysate by acetate-consuming Clostridium sp. S1 with high butyric acid yield and selectivity. (October 2016) - Kim, Minsun; Kim, Ki-Yeon; Lee, Kyung Min; Youn, Sung Hun; Lee, Sun-Mi; Woo, Han Min; Oh, Min-Kyu; Um, Youngsoon
Highlights: Acetate-consuming Clostridium sp. S1 was used for butyric acid production. Clostridium sp. S1 utilized glucose and mannose simultaneously. Clostridium sp. S1 utilized mixed sugars and acetic acid in softwood hydrolysate. High butyric acid yield and selectivity were achieved with softwood hydrolysate. Abstract: The aim of this work was to study the butyric acid production from softwood hydrolysate by acetate-consuming Clostridium sp. S1. Results showed that Clostridium sp. S1 produced butyric acid by simultaneously utilizing glucose and mannose in softwood hydrolysate and, more remarkably, it consumed acetic acid in hydrolysate. Clostridium sp. S1 utilized each of glucose, mannose, and xylose as well as mixed sugars simultaneously with partially repressed xylose utilization. When softwood (Japanese larch) hydrolysate containing glucose and mannose as the main sugars was used, Clostridium sp. S1 produced 21.17 g/L butyric acid with the yield of 0.47 g/g sugar and the selectivity of 1 (g butyric acid/g total acids) owing to the consumption of acetic acid in hydrolysate. The results demonstrate potential of Clostridium sp. S1 to produce butyric acid selectively and effectively from hydrolysate not only by utilizing mixed sugars simultaneously but also by converting acetic acid to butyric acid.